A sensor histidine kinase from a plant-endosymbiont bacterium restores the virulence of a mammalian intracellular pathogen - Chaves-Olarte, Esteban (2023)
Alphaproteobacteria include organisms living in close association with plants or animals. This interaction relies partly on orthologous two-component regulatory systems (TCS), with sensor and regulator proteins modulating the expression of conserved genes related to symbiosis/virulence. We assessed the ability of the exoS+Sm gene, encoding a sensor protein from the plant endosymbiont Sinorhizobium meliloti to substitute its orthologous bvrS in the related animal/human pathogen Brucella abortus. ExoS phosphorylated the B. abortus regulator BvrR in vitro and in cultured bacteria, showing conserved biological function. Production of ExoS in a B. abortus bvrS mutant reestablished replication in host cells and the capacity to infect mice. Bacterial outer membrane properties, the production of the type IV secretion system VirB, and its transcriptional regulators VjbR and BvrR were restored as compared to parental B. abortus. These results indicate that conserved traits of orthologous TCS from bacteria living in and sensing different environments are sufficient to achieve phenotypic plasticity and support bacterial survival. The knowledge of bacterial genetic networks regulating host interactions allows for an understanding of the subtle differences between symbiosis and parasitism. Rewiring these networks could provide new alternatives to control and prevent bacterial infection.